Effect of nitrogen on different genotypes of mungbean as affected by nitrogen level in low fertile soil (Bangladesh Journal of Agricultural Research, 2016)
A pot experiment was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during kharif- II season (August to November) of 2010 to find out the nitrogen acquisition and yield of mungbean genotypes affected by different levels of nitrogen fertilizer in low fertile soil. Ten mungbean genotypes viz. IPSA-12, GK-27, IPSA-3, IPSA-5, ACC12890053, GK-63, ACC12890055, BARI Mung-6, BUmug- 4 and Bina moog- 5 and six nitrogen fertilizer levels viz. 0, 20, 40, 60, 80 and 100 kg N ha-1 were included as experimental treatments. Results indicated that increasing applied nitrogenous fertilizer in low fertile soil increased nitrogen acquisition of mungbean which increased number of pods plant-1 and seeds pod-1 and finally increased yield of mungbean upto 60 kg N ha-1 irrespective of genotype and thereafter decreased. Genotype IPSA -12 produced the highest seed yield (14.22 g plant-1) at 60 kg N ha-1. The lowest yield (7.33 g plant -1) was recorded in ACC12890053 in control. From regression analysis, the optimum dose nitrogen for mungbean cultivation in the low fertile soil is 54 kg ha-1.Bangladesh J. Agril. Res. 40(4): 619-628, December 2015